Rheological characterization of asphalt binders used in strain relief asphalt mixtures (SRAM)1 (2017)
The use of 'interlayers' that tolerate high tensile and shear strain that exists above cracks in deteriorated pavements is becoming aninteresting solution to prevent reflective cracking. Recent advances in polymer technology have led to binders that can be used to produceinterlayer mixtures with good mechanical properties. In this study, two polymer-modified asphalt binders were evaluated, both from theproduction of strain relief asphalt mixtures used as interlayers in the field. The binder characterization was presented in two groups: (i) theempirical tests required in the Brazilian specification, and (ii) the rheological properties (frequency/temperature sweep and MSCR tests).Results showed that the difference in rheological properties of the asphalt binder used for strain relief asphalt mixtures did not follow thesame difference obtained according to the empirical tests of the Brazilian specification. The G*/sinδ and MSCR parameters (Jnr andpercentage of recovery) were able to differentiate the asphalt binders, but the MSCR parameters were more sensitive.